Large-Scale Meta-Analysis of Genes Encoding Pattern in Wilson’s Disease - Misra D.; Tiwari A.; Chaturvedi A. (My University, 2025)
In this paper, we propose an unsupervised learning approach with an objective to understand gene expressions for analysis of Wilson’s disease in the liver of Mus musculus organisms. We proceeded to obtain the best parameters for cluster division to correctly classify gene expression sets so as to capture the effect and characteristics of the disease in the genome levels of the organisms in the best possible way. The clustering proved beneficial in capturing the correct genetic analogy of Wilson’s disease. Analytical experiments were carried out using various clustering algorithms and were evaluated using performance metrics including silhouette score analysis and Calinski–Harabasz index. © 2019, Springer Nature Singapore Pte Ltd.